1982
DOI: 10.1161/01.cir.66.4.742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infarct location on the in-hospital prognosis of patients with first transmural myocardial infarction.

Abstract: SUMMARY We studied the in-hospital prognosis of 1105 patients who had their first transmural myocardial infarction; 611 patients (55.3%) had anterior myocardial infarction (AMI) and 494 (44.7%) had inferior myocardial infarction (IMI). Patients with IMI had a significantly lower in-hospital mortality rate (9.1% vs 15.6%, p = 0.0014) and significantly lower prevalences of congestive heart failure (39.4% vs 47.6%, p = 0.0066), cardiogenic shock (8.7% vs 12.6%, p = 0.0384) and conduction defects (left anterior he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…demonstrated a poorer prognosis (both early and late) for patients with anterior than for those with inferior infarction of similar size. However, they found no difference in the extent of infarction with either location of infarction, a finding that differs from other reports.5'6 Thanavaro et al 5 concluded that peak enzyme level and the location of the infarct each have independent influence on in-hospital prognosis of patients with myocardial infarction.…”
mentioning
confidence: 61%
“…demonstrated a poorer prognosis (both early and late) for patients with anterior than for those with inferior infarction of similar size. However, they found no difference in the extent of infarction with either location of infarction, a finding that differs from other reports.5'6 Thanavaro et al 5 concluded that peak enzyme level and the location of the infarct each have independent influence on in-hospital prognosis of patients with myocardial infarction.…”
mentioning
confidence: 61%
“…A recent report of 105 patients treated for initial myocardial infarction between 1971 and 1978 found an overall in-hospital mortality rate of 13%, with patients who had an anterior myocardial infarction having a higher mortality rate (15.6%) than did those with inferior infarcts (9.1%). 16 We would anticipate a slightly higher in-hospital mortality rate in our series since patients with previous myocardial infarctions were included, but the rate in our control group was 15%. It is therefore unlikely that better survival in the streptokinase group was due to an excessive mortality rate in the control group.…”
Section: Discussionmentioning
confidence: 89%
“…5,8,14,15 These factors have included age, extent of left ventricular dysfunction, infarct size, and development of heart failure. [41][42][43][44] It is notable that most of these factors result in sympathetic activation, 1,2,13 which in turn is believed to lead to an adverse outcome. 1,2,21 In addition, it is known that the increased mortality associated with ant-AMI occurs during the first few hours after the onset of infarction.…”
Section: Graham Et Al Sympathetic Drive and Site Of Infarctionmentioning
confidence: 99%